The Role of Teaching and Teacher Training in the Hiring and Promotion of Ph.D. Economists. (11th December 2017) - Allgood, Sam; Hoyt, Gail; McGoldrick, KimMarie
Abstract : Surveys suggest that a majority of graduate students seek academic positions after completing their degree. We survey groups involved in the job market to determine the roles of teaching and research in hiring and the subsequent success of new faculty. We find that while characteristics that signal research potential are highly valued by both graduate directors and department chairs, there are significant discrepancies in the extent that teaching is valued in the hiring process across institution types. Furthermore, although new faculty devote half of their time to teaching, only half of them agree that graduate school prepared them to teach.